UV-Visible Spectrophotometric Method Development and Validation of Itraconazole in Bulk and Capsule Formulation (International Journal of Advances in Pharmaceutical Analysis, 2016)
A simple, rapid, accurate and precise UV method was developed and validated for the estimation of Itraconazole in pharmaceutical dosage form. Spectroscopic method was carried out by using acidic ethanol as solvent. Itraconazole detection wavelength was set at 262nm for validation purpose linearity, accuracy, repeatability, precision, LOD, LOQ, and ruggedness parameters were studied. The linearity was found to be in the range of 2-12 g/ml.